The impact of brief lifestyle self-management education for the control of seizures. (28th March 2019) - Edward, Karen-leigh; Cook, Mark; Stephenson, John; Giandinoto, Jo-Ann
Abstract : Aim: this study examined a brief lifestyle self-management intervention, based on self-determination theory, to manage seizure frequency, and its effects on health-related quality of life and resilience in people with epilepsy aged over 18 years. Background: most people with epilepsy can identify factors that may trigger seizures and may try to avoid these; however, education from clinicians on this varies. Design: a cohort study with control design. Method: sixty participants were purposively sampled and allocated to an intervention or a control group. Results: moderate correlations were found, particularly between: resilience and satisfaction with life; medication adherence and psychological quality of life; and psychological quality of life and satisfaction with life. The mean seizure occurrences between the control and intervention groups were 12.71 (SD 24.55) and 6.76 (SD 13.40) respectively after the intervention. While the study was not powered to assess this, the intervention may be most effective regarding medication adherence and physical health quality of life. Conclusion: the relationship between self-efficacy and seizure management appeared to be strengthened by the programme. This study is the first known to measure resilience in relation to lifestyle self-management for seizure control in people with epilepsy. Relevance to practice: nurses are well placed to work with patients' strengths towards self-efficacy and potentially resilient coping.